Investigating The Role Of Religion In Shaping Moral Values And Social Norms - Muh. Afrilsah (Generasi Sains Indonesia, 2024)
The role of faith as a pillar of constructing ethical values and social norms continues to be historically present in different societies and cultures. Based on holy books and explanations by church leaders, religious teachings are sources of morality that guide personal behavior and relationship with others. The Ten Commandments of Judaism and Christianity and the Five Pillars of Islam prescribe doctrinal systems which govern issues of justice, compassion and responsibility. The moral orientation of the followers is further defined by the spiritual institutions, which through hierarchical institutions and charismatic leaders provide guidance, pastoral care and direction to the followers in times of crisis or societal change. The psychological and sociological approaches help to clarify how religion shapes moral values and norms. Cognitive theories highlight inherent tendencies which underpin faith in the sacred whereas sociological theories focus on the influence of religious institutions in promoting cohesion and behavioral control. Empirical studies reveal that there is a positive relationship between religious commitments and prosocial behavior but the effect sizes differ across traditions and cultures. In spite of the pluralism and diversity, interfaith dialogue and advocacy opens the possibilities to improve cooperation and understanding. Societies can use the transformative power of faith to create more inclusive, just, and caring societies by embracing diversity and developing dialogue.